EVALUATION OF BIOAGENTS FOR MANAGEMENT OF THE ONION PURPLE BLOTCH AND BULB YIELD LOSS ASSESSMENT UNDER FIELD CONDITIONS - P. M. YADAV,; K. B. RAKHOLIYA,; D. M. PAWAR, (The Bioscan, 2013)
Among the several diseases, purple blotch diseases of onion (Allium cepa L.) caused by Alternaria porri (Ellis) Cif. is one of the most destructive disease causing accountable losses of about 80 to 90 per cent. The results obtained on the field efficacy of different bioagents tested, Pseudomonas fluorescens--I (0.5%) was found most antifungal against A. porri and recorded significantly least mean disease intensity (37.19%) and gave maximum bulb yield (27183 kg/ha). Both the fungal and bacterial antagonists tested were also found effective against A. porri and recorded significantly reduced mean disease intensity thereby increased the bulb yield over unsprayed control. Based on incremental cost:benefit ratio (ICBR) of the bioagents spray treatments, P. fluorescens--I (ICBR, 1:13.87) was found economical and effective for the management of purple blotch of onion followed by Bacillus subtilis (ICBR, 1:12.93).